The Image of the Town: Medieval Sofia in Original Bulgarian Works from the 16th Century - Tsibranska-Kostova, Mariyana (Studia Ceranea, 2015)
The paper follows out the way of denomination and description of Sofia town in manuscripts from different genre during the period of the 15th-17th centuries, namely: the original hagiographic and hymnographic works of the men of letters from the 16th century Sofia literary school; the bedrolls; some marginal notes. This type of sources is rich enough not only for shaping the image of the town according to the linguistic evidences it was depicted with, but for making some general conclusions about its place in the so called “linguistic world view” as a semiotic model for approaching the lifestyle, the spiritual culture and the Bulgarian ethnic consciousness during the Ottoman domination. The chosen frame of time is not hazardous. It was a transitory period for both naming process and the creation of a new cultural situation, when the ideological and political dominant of the medieval town (the capital in particular) as an incarnation of the ruler’s institution has been already changed. Moreover, with the fall of Constantinople in 1453 the very Byzantine prototype of the town-mother and the spiritual center of the Orthodox world were destroyed. It is a matter of scholarly interest to give an idea on how another, different (new) model of the town was created in the Bulgarian cultural space to replace the past glorious vision, and how it reproduced the tradition. Briefly, how does the text create an image? It is a way to introduce the notion of hierotopy and its language in the original Bulgarian works of the given period. The specifically Bulgarian material inscribes itself in the common typological frames of the Balkan medieval culture in Ottoman times. The paradigm of holiness and the formation of the holly space require those aspects to be carried out in the light of the complex interdependency between the text, the image and the historical context – a binding triad that will be the base for the attending presentation.